STRATEGI PEMASARAN MIE KHAS ACEH PADA RESTORAN MIE ACEH RAZALI - Fani Sartika; Nadiya Nadiya; Rita Wahyu Ruyanti (Departemen Manajemen, Universitas Syiah Kuala, 2019)
AbstractThe success of a business can be determined by their ability to compete in seizing consumerswith the implementation of effective marketing strategies. The strength and weaknesses of acompany, combine with opportunities and threats that exist, can be a strong benchmark tomake a good marketing strategy. Culinary business is one of the business that can use a goodmarketing strategy to survive, considering the number of competitors is usually pretty high.This research highlighted on how a local culinary business can use a marketing strategyobtained by conducting a SWOT analysis. The object on this research is at Restoran Mie AcehRazali. The method used in this research is descriptive qualitative, by observing the object ofthe research to find their strengths, weaknesses, opportunities, and threats, while thequantitative analysis is used to find out the position of the company’s internal factor compareto the external factor, to find a marketing strategy to implement for the business using. Theresult of this research is the company is in a favorable situation with excellent strength andopportunities. The marketing strategy best to applied to support this condition is the growthorientedstrategy. Keywords Marketing strategy, Marketing mix, Cullinary business, SWOT analysis.